2021
DOI: 10.1007/s10734-021-00757-w
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be a technical university: organisational categories as reference points in higher education

Abstract: Classifications of higher education institutions into categories that are more or less clearly differentiated through prestige and status are legion in the world of higher education. The notion of parallel categories with comparable statuses, such as those of different types of universities, is however much less well understood. This paper investigates how universities navigate between such alternative categories. We examine boundary work and institutional change involving Swedish higher education institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…The development of knowledge-based economy became the new goal to the future prosperity of countries (Cader 2008;Muzaka 2019;Chorev and Ball 2022) Universities are one of the essential knowledge infrastructures experiencing even more pressure to compete with others not only on the local market but also be present and successful on international one. In these settings, universities in the Global South suffer identity crisis to the bigger extent as they are not the reference category, not in the realm of the expected universality (Albert and Whetten 1985;Hatch and Schultz 2002;Geschwind and Broström 2022). We argue that for universities in the periphery in the pursuit to establish international presence experience identity threat or destine to be labelled local and loose resources.…”
Section: Introductionmentioning
confidence: 85%
“…The development of knowledge-based economy became the new goal to the future prosperity of countries (Cader 2008;Muzaka 2019;Chorev and Ball 2022) Universities are one of the essential knowledge infrastructures experiencing even more pressure to compete with others not only on the local market but also be present and successful on international one. In these settings, universities in the Global South suffer identity crisis to the bigger extent as they are not the reference category, not in the realm of the expected universality (Albert and Whetten 1985;Hatch and Schultz 2002;Geschwind and Broström 2022). We argue that for universities in the periphery in the pursuit to establish international presence experience identity threat or destine to be labelled local and loose resources.…”
Section: Introductionmentioning
confidence: 85%
“…Australian researchers have commented upon the limits of impact assessment tools, being unable to fully understand more qualitative longitudinal forms of research impact [18]. Midterm adopter nations such as Poland and Sweden have remarked that there need not be a necessary logical link between research quality and the scale of impact [19], or how the very nomenclature of research institutions influence what types of impact claims become possible or not [20]. Notably, even Finland which, does not yet have an official research impact evaluation system as such, is nevertheless subject to have the very impact logic becoming all pervasive as well within its Higher Education system [21].…”
Section: Scope Of the Research Materialsmentioning
confidence: 99%
“…In terms of strategy, we observed that the universities benefited from discussing how to approach stakeholders in their local ecosystems and what to expect from those interactions. Technical universities are often entangled with an "ecosystem" of companies and other societal stakeholders (Jongbloed et al, 2008;Geschwind & Broström, 2022;Youtie & Shapira, 2008). This raises the question how such universities can collaborate with their respective ecosystem and what type of leadership may be expected from them.…”
Section: Case Study: the Euroteq Collidermentioning
confidence: 99%
“…We focus on the creation of alliances between technical universities (Geschwind & Broström, 2022) and our case study arises from one of them. The role of technical universities in society has come into sharp focus in recent years (see articles in Taebi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%